Rehabilitation of Narcotic Addictives: An Overview of Implementation and The Effort by Restorative Justice - Tofik Yanuar Chandra; Joko Sriwidodo; M.S. Tumanggor (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The progress of narcotics addictives is very concerning today and certainly requires comprehensive, integrated and continuous handling. However, in several cases, judges did not consider Article 103 of the Narcotics Law to provide rehabilitation for addicts and victims of narcotics abuse. Based on the background above, the problems that will be discussed in this study are: how is the implementation of the rehabilitation process for addicts and victims of narcotics abuse in Indonesia? And how does restorative justice apply to narcotics addicts through the rehabilitation process? This research is normative legal research with descriptive nature. The research results show that the implementation of rehabilitation for addicts and victims of narcotics abuse in Indonesia can be seen from the data for 2021 and 2022. It shows that the punishment for most narcotics addicts is imprisonment. So that efforts are needed from law enforcement officials prioritising rehabilitation for narcotics addicts to enforce restorative justice law. One of the efforts of restorative justice from law enforcement officials against narcotics addicts is the establishment of the Attorney General's Guidelines Number 18 of 2021 concerning the Settlement of Handling Cases of Crime of Narcotics Abuse through Rehabilitation with a Restorative Justice Approach as the Implementation of the Prosecutor's Dominus Litis Principle